Permasalahan Pembelajaran IPS yang Terdapat di SD : (Studi Kasus: SDN Ciwaktu) - Afinatussakinah, Sri; Nurzahra, Siti; Farhurohman, Oman (Educational Consultant & Counseling Career (EC3) Mataram, 2024)
The aim of this research is to find the problems that exist in the implementation of social studies learning in elementary schools. This research uses a qualitative method with a case study approach. This research was conducted at SDN Ciwaktu in the city of Serang using the interview method with teachers at SDN Ciwaktu. The results of this research show that students have problems both from external factors, namely school and family factors, and internal factors consisting of intelligence, interests, talents, motivation, emotion and mental health. The most important thing is the teacher's lack of ability to choose learning methods and media that suit the character of each student.